PENGARUH SIKAP, NORMA SUBYEKTIF DAN KONTROL PERILAKU YANG DIRASAKAN TERHADAP MINAT BERWIRAUSAHA DENGAN PENDEKATAN THEORY OF PLANNED BEHAVIOUR (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Unika Santo Thomas SU ) - Simanihuruk, Peran (UNIKA Santo Thomas, 2020)
The purpose of this study is to analyze the influence of attitudes, subjective norms and behavioral control that are felt partially and simultaneously on student interest in entrepreneurship. The benefit of this research is seeing the Theory of Planned Behavior Application to predict entrepreneurial students' interests and for other researchers, it is expected to be a reference and reference for conducting further research on the Theory of Planned Behavior Approach to find out entrepreneurial interests. The number of samples was 96 respondents, the method of data collection through questionnaires and documentation and analytical techniques used by applying the Theory of Planned Behavior model. The results of this study stated that attitude, subjective norms and behavioral control had a positive and partially significant effect on the interests of entrepreneurship in economics students. Simultaneously also showed that attitudes, subjective norms (subjective norms) and behavioral control (Percaived Behavior Control) have a positive and significant effect on entrepreneurial interest in students of the faculty of economics. The conclusions in this study indicate that student attitudes, subjective norms and perceived behavioral control have positive or partially simultaneous positive effects on entrepreneurial interest. Judging from the calculations it is known that the weights W1, W2 and W3 have positive values, which means that there is a positive influence on the Attitude, Subjective Norms, Trust Behavior Control variables on entrepreneurial interest, but the more dominant influence on entrepreneurial interest in students is the Attitude variable with position the value of attitude 23.32 is located between the numbers +2 and +3. Greater than subjective norm variables and perceived behavioral control. Suggestions that can be given to the managers of the Faculty of Economics, St. Thomas Catholic University of North Sumatra should increase the number of SKS Entrepreneurship courses and conduct various training to create products, how to determine the cost of products, how to sell / market products, how to promote products and distribute them to increase student insights so that the interest in entrepreneurship will form in his mind. With this, students who have graduated are not solely as job seekers but as field creators